SEEKING OUTSTANDING FEATURE ARTICLES: FIRST RESULTS OF THE OCEANOGRAPHY SURVEY - Kappel, Ellen S. (Oceanography (Washington, D.C.), 2022)
Over the summer, TOS conducted a survey of its membership, asking questions about how readers primarily access Oceanography (paper or online), what content they read the most, what subjects we should cover in the future, and whether they anticipate publishing an article in Oceanography in the next three years. The main purpose of the survey was to see if, on the magazine’s 35th anniversary, we needed to make some adjustments to maintain our readership. With the more than 100 responses submitted, spanning all career levels, I am pleased to report that overall, survey respondents seem to be content with our current format, and they offered many excellent thoughts on topics Oceanography should cover in the future and areas where we could do better.